1986
DOI: 10.1002/ddr.430090207
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular pharmacology of the cardiotonic, imazodan (Cl‐914)

Abstract: of the cardiotonic, imazodan (CI-914). Drug Dev. Res. 9:143-157, 1986. lmazodan is a novel pyridazinone derivative. It was evaluated in excised cardiac tissue, anesthetized dogs and monkeys, and conscious dogs. Imazodan, 10-5-10-3M, produced dose-dependent increases in guinea pig atrial and rabbit papillary muscle contractility. In anesthetized dogs and rhesus monkeys, imazodan, 0.001-1 .O mg/kg IV, produced dosedependent increases of 10-150% in myocardial contractility (dPldt max of left ventricular pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The initial morphological changes induced by these compounds has been characterized following a single high dose of a potent PDE III inhibitor, SK&F 95654, to dogs (17), but the pathogenesis of this toxic effect has not been determined. Furthermore, although PDE III inhibitors are potent vasodilators at pharmacological doses (6,11,30) the hemodynamic effects of these agents at toxicological doses have not been fully defined.…”
Section: Introductionmentioning
confidence: 99%
“…The initial morphological changes induced by these compounds has been characterized following a single high dose of a potent PDE III inhibitor, SK&F 95654, to dogs (17), but the pathogenesis of this toxic effect has not been determined. Furthermore, although PDE III inhibitors are potent vasodilators at pharmacological doses (6,11,30) the hemodynamic effects of these agents at toxicological doses have not been fully defined.…”
Section: Introductionmentioning
confidence: 99%
“…The invivo cardiovascular effects of imazodan were initially evaluated in the anesthetized open-chest dog. In this model imazodan produced a significant dose-related increase in myocardial contractility [67]. This increase is accompained by a dose-dependent decrease in blood pressure, with a minimal increase in heart rate.…”
Section: In-vivo Studiesmentioning
confidence: 70%
“…Imazodan (CI-914) was synthesized in 1980, and initial studies in isolated guinea-pig left atria revealed that it exerted a positive inotropic effect [66]. Subsequent studies showed that imazodan also exerted a cardiotonic effect when administered intravenously to the anesthetized dog or orally to the conscious dog [67].…”
Section: Imazodan: Pharmacological Effects and Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct cardiac stimulant properties of imazodan have been characterized in vitro using left atrial tissue excised from guinea pigs and right ventricular papillary muscle excised from rabbits (10). The effects of imazodan and of the reference cardiotonic agents amrinone and ouabain on peak developed tension of these tissues are summarized in Tables 1 and 2.…”
Section: In Vitromentioning
confidence: 99%